Flying the Rainbow Flag at the United Nations - Douglas Sanders (Journal of Southeast Asian Human Rights, 2021)
Issues of sexual orientation and gender identity were raised in two of the United Nations intergovernmental world conferences on women, 1985 and 1995, and in the Vienna world conference on human rights in 1993. From 2006 a number of LGBTI Non-Governmental Organizations gained ongoing ‘consultative status’ from the Economic and Social Council allowing access to regular UN human rights events. Leading human rights NGOs, such as Amnesty International and Human Rights Watch began to address LGBTI issues. The Human Rights Council condemned violence and discrimination on grounds of sexual orientation and gender identity in 2011 and later authorized an independent expert, whose mandate was renewed for a second term. The UNDP “Being LGBT in Asia” program has been active in eight Asian states, including five in ASEAN: Cambodia, Indonesia, Philippines, Thailand, and Vietnam. Strong support came from Ban Ki-moon as UN Secretary-General, as well as from the Office of the UN High Commissioner for Human Rights and other agencies.